VIDEO SEBAGAI E-PORTFOLIO MAHASISWAUNTUK MENINGKATKAN KETERAMPILAN MAHASISWA - Giandari Maulani; Untung Rahardja; Lalita Tri Adila (Universitas Raharja, 2016)
The development of science and technology information in the era of globalization so advanced. This phenomenon results in a change in all aspects of life, including one of them is the educational aspect. The use of technology in education is done in order to improve the efficiency and effectiveness of the learning process. However, the growing use of technology is not widely used lecturers to change the way student assessment. Student assessment is focussed on learning outcomes not only of the process of change as a result of the student's ability to learn. the use of portfolios also require adequate storage space and requires no small cost. Therefore we need a valuation technique that directs faculty to assess student skills or psychomotor aspects. By using the technique of portfolio assessment with the use of the video as a result be able to answer all the problems that exist. This journal will discuss how assessment techniques, portfolio assessment, the transition of the portfolio into an e-portfolio, the use of video as a medium of e–portfolio also discusses the problems encountered in the portfolio assessment. Besides, there are advantages and disadvantages of the use of video as a medium of e–portfolio. In the implementation of this journal featuring two case studies of e–portfolio with student video uploaded on YouTube and shown in the playlist in Magics Channel owned Perguruan Tinggi Raharja